PECULIARITIES OF USING THE EDUCATIONAL DIALOGUE AS A MEANS OF FORMING THE COMMUNICATIVE CULTURE OF FUTURE TEACHERS OF FOREIGN LANGUAGES (Pedagogy of Higher and Secondary Education, 2009)
This article deals is paid to the usage of the educational dialogue at the term forming of the communicative culture of future teachers of foreigns languages.